2013
DOI: 10.1017/s0959269513000045
|View full text |Cite
|
Sign up to set email alerts
|

Verbo-pictorial metaphor in French advertising

Abstract: ab st rac tIn the last thirty years the development of the Cognitive Metaphor Theory (e.g. Lakoff, 1987Lakoff and Johnson, 1999) has led to vast research into metaphor. The study of linguistic metaphor was followed by a body of work into pictorial metaphor (Forceville, 1994(Forceville, , 1996 and multimodal metaphor (Forceville, 2007(Forceville, , 2008(Forceville, , 2009). In the present contribution we explore the use of verbo-pictorial metaphors in advertising through a corpus of French print ads. Startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Multimodality contributes to the persuasion by providing the wanted features in more than one mode [ 26 ]. Previous studies reported that multimodal metaphors are used frequently since they contribute to the persuasive and communicative functions of advertisements (e.g., [ [14] , [41] , [50] ]). One of the observations about the food industry in the collected corpus is that the target domain (the advertised product) is always present in the pictorial context in all of the advertisements except for two cases as shown previously.…”
Section: Analysis Of the Datamentioning
confidence: 99%
“…Multimodality contributes to the persuasion by providing the wanted features in more than one mode [ 26 ]. Previous studies reported that multimodal metaphors are used frequently since they contribute to the persuasive and communicative functions of advertisements (e.g., [ [14] , [41] , [50] ]). One of the observations about the food industry in the collected corpus is that the target domain (the advertised product) is always present in the pictorial context in all of the advertisements except for two cases as shown previously.…”
Section: Analysis Of the Datamentioning
confidence: 99%
“…I n the last few years metaphor research from a cognitive perspective has extended to nonverbal metaphor in different genres (e.g. Forceville & Urios-Aparisi, 2009), including advertising (e.g., Caballero, 2009;Forceville, 1996Forceville, , 2007Forceville, , 2008aForceville, , 2009aForceville, , 2009bForceville, , 2012McQuarrie & Philips, 2008;Negro, 2013b;Urios-Aparisi, 2009;Velasco-Sacristán & Fuertes-Olivera, 2006a, 2006b, comics, manga and animation (Eerden, 2009;Forceville, 2008b;Shinohara & Matsunaka, 2009), and politics (e.g., Charteris-Black 2004Musolff, 2004;Sharifian & Jamarani, 2013). Cognitive approaches to political cartoons have focused on the use and (usually negative) connotations of visual metaphors (e.g., Abdel-Raheem, 2015Bounegru & Forceville, 2011;El Refaie 2003Gorska, 2017;Negro, 2013aNegro, , 2014Sharifian & Jamarani, 2013;Schilperoord & Maes, 2009;Yus 2009).…”
Section: Isabel Negro Alousquementioning
confidence: 99%
“…Many of these metaphors are also likely to be visual or multimodal (Forceville, 2009) like in Figure 1 where the metaphor of 'letting go' is expressed with both words and pictures. However, our understanding of how (multimodal) metaphors are constructed and communicated in motivational posters lags well behind other genres such as films, cartoons, and advertisements, where researchers have already gone from describing their contents to evaluating their effects (Alousque, 2014;Jeong, 2008;Landau, Nelson, & Keefer, 2015;Pérez-Sobrino, 2016). Basic descriptive questions concerning topics, vehicles 1 and the construction of topic-vehicle relationships in motivational posters remain unanswered.…”
Section: Introductionmentioning
confidence: 99%